Method for producing carbon material from agglomerated lignin

By forming an agglomerated lignin-thermoset resin material, the problems of lignin deformation and dust formation in the heating step are solved, and the feasibility of material shape maintenance and large-scale manufacturing is achieved.

CN119731120APending Publication Date: 2025-03-28STORA ENSO OYJ
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380060196.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-17
Filing Date
2023-08-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, when using lignin to produce carbon-rich materials, there are problems of plastic deformation/melting, violent expansion and foaming in the heating step, and dust formation increases processing risks and limits the processability of the industrial scale.

Method used

By forming an agglomerated lignin-thermosetting resin material, the thermosetting resin is used to contact and cure with lignin to form a material with a specific particle size distribution, thereby maintaining the shape during heat treatment, avoiding melting and expansion, and reducing dust formation.

Benefits of technology

The shape of lignin is maintained during heat treatment, avoids melting and expansion, reduces the risk of dust formation, improves the processability of the material, and is suitable for large-scale manufacturing.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for producing an agglomerated lignin-thermoset resin material. The method includes the steps of providing lignin, providing at least one thermoset resin, forming an agglomerated lignin-thermoset resin material, and curing the agglomerated lignin-thermoset resin material. The invention also relates to a method for producing a carbon material comprising a heat treatment of the agglomerated lignin-thermoset resin material to obtain the carbon material. The obtained carbon material is suitable for use as an active material in a negative electrode of a secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an agglomerated lignin-thermosetting resin material and an agglomerated lignin thermosetting resin material. The present invention also relates to a method for producing a carbon material from the agglomerated lignin-thermosetting resin material and a carbon material obtainable by the method. The present invention further relates to a negative electrode for a secondary battery comprising the carbon material as an active material. The present invention further relates to the use of the carbon material as an active material in a negative electrode for a secondary battery. Background Art

[0002] Secondary batteries, such as lithium-ion batteries, are batteries that can be charged and discharged multiple times, i.e. they are rechargeable batteries. In lithium-ion batteries, lithium ions flow from the negative electrode through the electrolyte to the positive electrode during discharge, and back during charging. Typically, lithium compounds, particularly lithium metal oxides such as lithium nickel manganese cobalt oxide (NMC) or alternatively lithium iron phosphate (LFP) are used as positive electrode materials, and carbon-rich materials are used as negative electrode materials.

[0003] Graphite (natural or synthetic) is currently used as the negative electrode material in most lithium-ion batteries. Alternatives to graphite are amorphous carbon materials, such as hard carbon (non-graphitizable amorphous carbon) and soft carbon (graphitizable amorphous carbon), which lack long-range graphitic order. Amorphous carbon can be used as the sole active electrode material or in a mixture with graphite (and / or other active materials).

[0004] Amorphous carbon can be derived from lignin. Lignin is an aromatic polymer, which is the main component in wood, for example, and is one of the most abundant carbon sources on Earth. In recent years, with the development and commercialization of technologies for extracting lignin in highly purified, solid and particularized forms from pulp manufacturing processes, it has attracted significant attention as a possible renewable alternative to the main aromatic chemical precursors currently derived from the petrochemical industry. Amorphous carbon derived from lignin is typically non-graphitizable, that is, hard carbon.

[0005] Lignin has a complex chemical structure, which depends largely on its source, such as the type of plant or tree from which it is obtained. The properties of lignin, such as its glass transition temperature, vary significantly depending on the chemical structure, composition, and any impurities present in the lignin. In particular, lignin obtained from hardwoods such as Eucalyptus has a relatively lower glass transition temperature than lignin obtained from softwoods.

[0006] Today, the most commercially relevant source of lignin is kraft lignin obtained from hardwood or softwood by the kraft process. The lignin can be separated from alkaline black liquor using, for example, a membrane or ultrafiltration. A common separation process is described in WO2006031175A1. In this process, lignin is precipitated from alkaline black liquor by reducing the pH level of the black liquor, usually by adding carbon dioxide, and then filtered out. In the next step, the lignin filter cake is re-slurried and washed under acidic conditions, usually using sulfuric acid. The precipitated and washed lignin can be used as is or further dried.

[0007] One problem with using lignin as a precursor of carbon-rich materials is that it is inappropriate to directly use lignin in fine powder form because it shows undesirable thermoplastic behavior and a strong tendency to form dust. During the thermal conversion of lignin powder into carbon-rich materials, lignin undergoes plastic deformation / melting, violent expansion and foaming. With regard to the demand for equipment size and process throughput and intermediate processing, this severely limits the processability of lignin on an industrially relevant scale. In addition, dust formation increases the risk of dust explosions during processing.

[0008] The above-mentioned problems with undesirable thermoplastic behavior are particularly evident when processing lignin with a low glass transition temperature, such as lignin obtained from hardwood. For lignin with a low glass transition temperature, problems associated with melting, softening and decomposition will begin at relatively low temperatures.

[0009] WO2021250604 A1 describes a method for forming agglomerated lignin from lignin powder. The agglomerated lignin is further stabilized by thermal oxidation before heat treatment and conversion into a carbon material. By using subsequent thermally stabilized agglomerated lignin, the problems of deformation / melting and dust formation are further reduced. However, when using lignin with a low melting point, melting and fusion may occur before the temperature required for thermal stability is reached.

[0010] Therefore, no matter how the source of the lignin is, there is still room for improvement in the method for producing the lignin material of agglomeration and the method for producing carbon-rich material by lignin. The method should avoid lignin from experiencing plastic deformation / melting, violent expansion and foaming during any heating step and when lignin is converted into carbon-rich material. The method should also avoid forming dust during lignin processing. In addition, the method should be used in large-scale manufacturing. Summary of the invention

[0011] It is an object of the present invention to provide an improved process for producing carbon-rich materials which allows the use of renewable carbon sources and which obviates or mitigates at least some of the disadvantages of prior art processes.

[0012] Another object of the present invention is to provide a method for obtaining improved carbon-rich materials starting from lignin, which carbon-rich materials are suitable for use as active materials in the negative electrode of secondary batteries, such as lithium-ion batteries.

[0013] Another object of the present invention is to provide a method for obtaining agglomerated lignin which can be subjected to subsequent thermal treatment without melting / fusion or foaming.

[0014] Another object of the present invention is to provide a method for producing carbon-rich materials from lignin, which method allows thermal treatment of lignin, whatever its origin, while maintaining the shape.

[0015] Another object of the present invention is to provide a method for avoiding dust formation during the processing of lignin in powder form.

[0016] Another object of the present invention is to provide a method for producing carbon-rich materials from lignin, which method is scalable and thus suitable for large-scale manufacturing.

[0017] The above objects and other objects as will be appreciated by skilled artisans from this disclosure are achieved through various aspects of the present disclosure.

[0018] According to a first aspect, the present invention relates to a method for producing an agglomerated lignin-thermosetting resin material, wherein the method comprises the following steps:

[0019] -providing lignin;

[0020] - providing at least one thermosetting resin;

[0021] - forming an agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm, wherein said forming involves contacting said lignin with said at least one thermosetting resin; and

[0022] - Curing the agglomerated lignin-thermosetting resin material.

[0023] It has been surprisingly found that by forming an agglomerated lignin-thermosetting resin material, a lignin material is obtained which can be heat treated after solidification while maintaining its shape, avoiding melting / expansion and deformation. Dust formation during the processing of lignin is also reduced by the method of the invention. Surprisingly, the method of the invention also promotes the thermal processing of lignin with a low glass transition temperature, such as lignin obtained from hardwood.

[0024] According to a second aspect, the present invention relates to an agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm. The agglomerated lignin-thermosetting resin material according to the second aspect can be obtained by a method according to the first aspect.

[0025] According to a third aspect, the present invention relates to a method for producing a carbon material, the method comprising the following steps:

[0026] - providing an agglomerated lignin-thermosetting resin material obtainable by the method according to the first aspect, or an agglomerated lignin-thermosetting resin material according to the second aspect; and

[0027] - subjecting the agglomerated lignin-thermosetting resin material to a heat treatment at one or more temperatures ranging from 300°C to 3000°C, wherein the heat treatment is carried out for a total time ranging from 30 minutes to 10 hours, to obtain a carbon material.

[0028] It has been surprisingly found that by providing lignin in the form of an agglomerated lignin-thermosetting resin material, the lignin material can be heat treated while maintaining shape, avoiding melting / expansion and deformation. The resulting carbon material is suitable for use in, for example, energy storage applications, such as active materials in the negative electrode of a secondary battery.

[0029] According to a fourth aspect, the present invention relates to a carbon material obtainable by a method according to the third aspect.

[0030] According to a fifth aspect, the present invention relates to a negative electrode for a secondary battery, the negative electrode comprising, as an active material, a carbon material obtainable by the method according to the third aspect.

[0031] According to a sixth aspect, the present invention relates to the use of a carbon material obtainable by the method according to the third aspect as active material in a negative electrode of a secondary battery. DETAILED DESCRIPTION

[0032] One step of the method according to the first aspect involves providing lignin. Throughout this disclosure, the term "lignin" is intended to refer to any type of lignin that can be used as a carbon source for preparing carbon-rich materials. Examples of the lignin are, but are not limited to, lignin obtained from plant raw materials such as wood, such as softwood lignin, hardwood lignin, and lignin from annual plants. Moreover, the lignin can be chemically modified.

[0033] Preferably, the lignin has been purified or separated before being used in the process according to the invention. The lignin may be separated from black liquor and optionally further purified before being used in the process according to the invention. The purification typically results in a purity of the lignin of at least 90%, preferably at least 95%, more preferably at least 98%, based on the dry weight of the lignin material. Thus, the lignin material used in the process according to the invention preferably contains less than 10%, preferably less than 5%, more preferably less than 2% of impurities, such as cellulose, carbohydrates and inorganic compounds, based on the dry weight of the lignin material.

[0034] The lignin can be obtained by different extraction methods, such as an organosolv process or a kraft process. Preferably, the lignin used in the method of the present invention is a kraft lignin, i.e. a lignin obtained by the kraft process. The kraft lignin can be obtained from hardwood or softwood.

[0035] Kraft lignin is readily available as a by-product from pulp production by the kraft process. From a sustainability point of view, it is beneficial to utilize kraft lignin that would otherwise typically be discarded. Thus, by utilizing kraft lignin, a more sustainable process can be achieved. Kraft lignin can be extracted on an industrial scale by known and established processes that produce lignin of consistent quality. Thus, kraft lignin is suitable for use in large-scale processing, where the repeatability of the process is highly important. The extracted kraft lignin can be readily chemically modified or cross-linked, which makes it easier to further facilitate processing.

[0036] The lignin can be obtained by the process disclosed in WO2006031175 A1, generally referred to as the LignoBoost process. Typically, the process involves the following steps: precipitating lignin from alkaline black liquor by acidification; separating the precipitated lignin; and re-slurrying the lignin at least once under acidic conditions. The obtained lignin can be dried and pulverized and thus provided as solid particles.

[0037] The method according to the first aspect also involves providing at least one thermosetting resin. As used herein, the term "thermosetting resin" refers to a resin that is irreversibly hardened by curing. The term "thermosetting resin" is not intended to cover the precursors of thermosetting resins, but only covers the resins obtained by the reaction of one or more precursors. The type of thermosetting resin is not particularly limited, and any suitable thermosetting resin can be used in the method according to the present invention. In some embodiments, the at least one thermosetting resin is selected from furan resins such as polyfurfuryl alcohol, epoxy-based resins, phenolic resins such as bakelite, vinyl esters, melamine resins and polyimides. Preferably, the thermosetting resin is a furan resin such as polyfurfuryl alcohol.

[0038] The at least one thermosetting resin may be provided in liquid form, or in solid form, for example in powder form. The thermosetting resin may be diluted using any suitable solvent. The thermosetting resin may also contain at least one additive. The at least one additive may, for example, affect the properties of the thermosetting resin, or it may have an effect on the agglomerated lignin-thermosetting resin material.

[0039] In some embodiments, a thermosetting resin is provided. In some embodiments, more than one thermosetting resin is provided, such as two different types of thermosetting resins, or three different types of thermosetting resins. The different types of thermosetting resins can also be in different forms, such as at least one in liquid form and at least one in solid form.

[0040] The method according to the first aspect also involves forming an agglomerated lignin-thermosetting resin material, the agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm. The forming step involves contacting the lignin with the at least one thermosetting resin. As used herein, the term "lignin-thermosetting resin material" refers to a material comprising both lignin and at least one thermosetting resin. The lignin-thermosetting resin material may optionally include at least one additive. The lignin-thermosetting resin material of the present invention is a composite material comprising lignin and at least one thermosetting resin. The lignin is contacted with the thermosetting resin without contacting with a precursor of the thermosetting resin. Therefore, the lignin-thermosetting resin material of the present invention is not a thermosetting resin based on lignin. For example, if lignin is reacted with a precursor of a thermosetting resin, such a thermosetting resin based on lignin will be obtained. In the present invention, the lignin is not modified by contacting with the thermosetting resin, and the main polymeric structure of the lignin is not changed.

[0041] As used herein, the term "forming" refers to the process of forming an agglomerated lignin-thermosetting resin material by contacting lignin with at least one thermosetting resin so as to obtain an agglomerated lignin-thermosetting resin material. As used herein, the term "contacting" refers to the process of placing lignin and at least one thermosetting resin in close proximity to each other. In some embodiments, there is no or substantially no chemical reaction between lignin and the at least one thermosetting resin in the contacting step. In other embodiments, some chemical reactions may occur between the reaction sites of the thermosetting resin and the lignin in the contacting step.

[0042] In a preferred embodiment of the invention, the agglomerated lignin thermosetting resin material comprises 80 to 99 wt %, or 90 to 99 wt %, or 95 to 99 wt % lignin based on the total weight of the agglomerated lignin thermosetting resin material. In such an embodiment, the amount of lignin in the contacting step is always significantly higher than the amount of the thermosetting resin. Therefore, if some chemical reaction occurs between the thermosetting resin and the lignin, only a minor portion of the lignin in the agglomerated lignin-thermosetting resin material will have reacted, while the major portion of the lignin will remain unchanged through the contacting step.

[0043] As used herein, the term "agglomerated," such as "agglomerated lignin" and "agglomerated lignin-thermosetting resin material," refers to macroscopic particles that in turn contain clustered smaller particles of lignin or lignin and thermosetting resin.

[0044] Depends on the lignin provided, the forming step may or may not involve an agglomeration step. The forming step may involve coating agglomerated lignin with at least one thermosetting resin, or it may involve mixing lignin powder and at least one thermosetting resin powder and subsequently forming an agglomerate by the mixture. In some embodiments, the total amount of thermosetting resin in the agglomerated lignin-thermosetting resin material is based on the total dry weight of the agglomerated lignin-thermosetting resin material at 1 wt % to 70 wt %, such as 1 wt % to 50 wt %, or 1 wt % to 20 wt %, or 1 wt % to 10 wt %. "Total amount of thermosetting resin" means the total amount of all thermosetting resins present in the lignin-thermosetting resin material.

[0045] In a preferred embodiment, the total amount of thermosetting resin in the agglomerated lignin-thermosetting resin material is in the range of 1 wt % to 20 wt % or 1 wt % to 10 wt % or 1 wt % to 5 wt % based on the gross weight of the agglomerated lignin-thermosetting resin material. It is advantageous to form an agglomerated lignin-thermosetting resin material comprising a low amount of thermosetting resin, because the material mainly comprises the material from renewable resources in this case, and a more sustainable method can be achieved. The cost of lignin is typically lower than the cost of thermosetting resin. Based on the gross weight of the agglomerated lignin-thermosetting resin material, a low amount of thermosetting resin, for example 1 wt % to 5 wt %, will fully improve the thermal properties of the agglomerated material, to avoid the melting of lignin during thermal treatment.

[0046] In some embodiments, the one or more thermosetting resins may be obtained from renewable sources. In such embodiments, the lignin-thermosetting resin material may be completely renewable.

[0047] The agglomerated lignin-thermosetting resin material comprises 30 to 99 wt %, or 50 to 99 wt %, or 80 to 99 wt %, or 90 to 99 wt % lignin based on the total weight of the agglomerated lignin-thermosetting resin material. Preferably, the agglomerated lignin-thermosetting resin material comprises 80 to 99 wt %, or 90 to 99 wt %, or 95 to 99 wt % lignin based on the total weight of the agglomerated lignin-thermosetting resin material.

[0048] The agglomerated lignin-thermosetting resin material may comprise only lignin and a thermosetting resin, or may comprise lignin, a thermosetting resin and at least one additive. Based on the total weight of the agglomerated lignin-thermosetting resin material, the amount of the at least one additive is typically small, for example, below 5 wt %, or below 2 wt %.

[0049] The method according to the first aspect also relates to curing the agglomerated lignin-thermosetting resin material. Curing can be carried out at room temperature and / or elevated temperature. By increasing the temperature, curing becomes faster. The temperature used during curing also depends on the type of thermosetting resin.

[0050] In some embodiments, curing is carried out at one or more temperatures in the range of 20°C to 250°C, and wherein curing is carried out for a total time of at least 30 minutes, i.e., the residence time of the agglomerated lignin-thermosetting resin material in the device for curing is at least 30 minutes. The total time for curing is preferably less than 24 hours. During curing, irreversible hardening of the at least one thermosetting resin occurs. After curing, an agglomerated lignin thermosetting resin material that does not change its shape during any subsequent thermal treatment is obtained. Moreover, adding the thermosetting resin material to the agglomerated lignin further reduces the melting / expansion behavior of the lignin during heating.

[0051] In some embodiments, curing is performed at one or more temperatures in the range of 20° C. to 250° C., such as 20° C. to 200° C., or 20° C. to 150° C., or 50° C. to 150° C., for a total time of at least 30 minutes. Preferably, curing is performed at one or more temperatures in the range of 20° C. to 150° C., or 50° C. to 150° C. for a total time of at least 30 minutes. In such embodiments, the lignin does not exhibit melting / swelling behavior, or exhibits only minor melting / swelling behavior.

[0052] In embodiments where the agglomerated lignin is coated with the at least one thermosetting resin, the inventors believe that after curing, the hardened thermosetting resin will retain the lignin within the agglomerated lignin-thermosetting resin material, thereby preventing melting / expansion of the lignin during any subsequent thermal treatment at temperatures where the lignin would normally exhibit melting / expansion behavior.

[0053] In embodiments where lignin is mixed with the at least one thermosetting resin prior to forming the agglomerated material, it is believed that a matrix of the thermosetting resin may be formed after curing, wherein the lignin is contained within the matrix such that melting / expansion of the lignin is prevented during any subsequent thermal treatment at temperatures where the lignin would normally exhibit melting / expansion behavior.

[0054] In some embodiments, lignin may react with the thermosetting resin during curing. In other embodiments, the only reaction that occurs during curing is within the thermosetting resin. In some embodiments, there will be reactions between lignin polymer chains during curing. Therefore, during curing, crosslinking reactions will occur within the thermosetting resin, and there may also be crosslinking reactions between the thermosetting resin and lignin and / or between different lignin polymer chains. The crosslinking reactions between lignin and thermosetting resin and between different lignin polymer chains will reduce the melting / expansion behavior of lignin during any subsequent heating steps at temperatures where lignin typically exhibits melting / expansion behavior. Crosslinking within the thermosetting resin can produce physical restrictions that prevent the melting / expansion of lignin.

[0055] Besides the crosslinking of the thermosetting resin, the reactions which occur during curing depend, for example, on the temperature and the type of thermosetting resin used.

[0056] In some embodiments, the curing is performed using the same temperature throughout the curing step. In some embodiments, the curing is performed at room temperature for a total time of at least 30 minutes.

[0057] In some embodiments, curing is carried out at a variable temperature, such as using a gradually increased temperature or using a temperature gradient. In some embodiments, curing is carried out in several steps at different temperatures. Temperature can be increased from one step to a subsequent step by a temperature ramp or gradient. For example, curing can be carried out by: the agglomerated lignin-thermosetting resin material is heated to a first temperature in the range of 20°C to 250°C, such as 20°C to 200°C, or 20°C to 150°C, or 50°C to 150°C, then heated to a second temperature in the range of 20°C to 250°C, such as 20°C to 200°C, or 20°C to 150°C, or 50°C to 150°C, etc., and at each selected temperature, a certain amount of time is maintained, such as in the range of 10 minutes to 3 hours. By curing in several steps at different temperatures, the improved crosslinking of the agglomerated lignin-thermosetting resin material cured is achieved. By improving the crosslinking during the curing of the agglomerated lignin-thermosetting resin material, the properties of the carbon material obtained by heat treatment of the agglomerated lignin-thermosetting resin material are improved in terms of microporosity. In addition, since the curing process can be carried out in a more controlled manner, the risk of cracking of the agglomerated lignin-thermosetting resin material during curing is reduced.

[0058] In some embodiments, an acidic catalyst is added to the at least one thermosetting resin material, and the curing of the agglomerated lignin-thermosetting resin material is catalyzed by the acidic catalyst. In one embodiment, the acidic catalyst is selected from sulfuric acid, maleic anhydride or p-toluenesulfonic acid. Curing using a catalyst can be carried out at room temperature and / or at an elevated temperature. Curing is faster at an elevated temperature.

[0059] Curing can be accomplished using both a catalyst and elevated temperature, or by a catalyst alone, or by elevated temperature alone.

[0060] After forming and curing, an agglomerated lignin-thermosetting resin material is obtained, the agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm. Preferably, the particle size distribution is such that at least 90% by weight, more preferably at least 95% by weight of the particles have a diameter in the range of 0.2 mm to 5.0 mm. More preferably, at least 90% by weight, more preferably at least 95% by weight of the particles have a diameter in the range of 0.5 mm to 2 mm.

[0061] The agglomerated lignin thermosetting resin material preferably has a density of 0.5 g / cm 3 Up to 0.7g / cm 3 In the range of 0.5 g / cm 3 Up to 0.6g / cm3 The bulk density is within the range of .

[0062] In one embodiment of the invention, the lignin in the method according to the first aspect is provided in the form of agglomerated lignin, the agglomerated lignin having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm. The agglomerated lignin is preferably obtained by a method comprising the following steps:

[0063] a) providing lignin in powder form, wherein the lignin in powder form has a particle size distribution such that at least 80% by weight of the particles have a diameter of less than 0.2 mm and a moisture content of less than 45% by weight;

[0064] b) compacting the lignin powder of step a);

[0065] c) crushing the compacted lignin obtained in step b) to obtain agglomerated lignin; and

[0066] d) optionally sieving the agglomerated lignin obtained in step c) to remove particles having a particle size below 100 μm, thereby obtaining agglomerated lignin having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm.

[0067] Preferably, the powdered lignin is dried before compaction. The drying of the lignin is carried out by methods and equipment known in the art. The powdered lignin used in step a) has a moisture content of less than 45% by weight. Preferably, before compaction according to the present invention, the moisture content of the lignin is less than 25% by weight, preferably less than 10% by weight, more preferably less than 8% by weight. In one embodiment, before compaction according to the present invention, the moisture content of the lignin is at least 1% by weight, such as at least 5% by weight. The temperature during drying is preferably in the range of 80°C to 160°C, more preferably in the range of 100°C to 120°C.

[0068] The lignin powder obtained after drying has a broad particle size distribution in the range of 1 μm to 2 mm, which is significantly skewed towards the micrometer range, meaning that a significant proportion of the particles have a diameter in the range of 1 to 200 micrometers.

[0069] The compaction of the lignin is preferably carried out by roller compaction. The roller compaction of lignin can be achieved by a roller compactor to agglomerate the lignin particles. In the compaction step, an intermediate product is generated. Here, fine lignin powder is usually fed by a hopper and transported to a compaction zone by means of a horizontal or vertical feed screw, wherein the material is compacted into a thin sheet by a compaction roller with a defined gap. By controlling the feed screw speed, the pressure in the compaction zone develops, and a thin sheet with uniform density can be obtained. The pressure development in the compaction zone can preferably be monitored and controlled by the rotation speed of the compaction roller. When the powder is dragged between the rollers, it enters a place called the roller gap area, wherein the density of the material increases and the powder is converted into a thin sheet or ribbon. The roller used has a cavity. The depth of each cavity for roller compaction is 0.1mm to 10mm, preferably 1mm to 8mm, more preferably 1mm to 5mm or 1mm to 3mm. The specific pressure applied during said compacting may vary depending on the equipment used for compacting, but may be in the range of 1 kN / cm to 100 kN / cm. Suitable equipment for carrying out compaction is known in the art.

[0070] After compaction, crushing is preferably performed. In the crushing step, the intermediate product from the compaction step is subjected to crushing or grinding, for example by means of a rotary granulator, a cage mill, an impact mill, a hammer mill, a crusher mill and / or a combination thereof. During this step, further intermediate products are generated.

[0071] After crushing, the crushed material is preferably subjected to a screening step to remove fine material. In addition, large materials, such as agglomerates with a diameter greater than 5.0 mm, can be removed and / or recycled back to the crushing step. In the screening step, the intermediate product from the crushing step is screened by physical classification, such as screening, also known as screening, to obtain a product, which is an agglomerated lignin with a defined particle size distribution set by the porosity of the sieve or screen in this step. The sieve or screen is selected so that most particles with a diameter below 100 (or 500) μm pass through the sieve and are discarded, and preferably return to the compacting step, while most particles with a diameter above 100 (or 500) μm are retained and undergo a subsequent heating step according to the process of the present invention. The screening can be performed in more than one step, that is, the screening can be performed so that the crushed material from the crushing step passes through more than one sieve or screen in succession.

[0072] In one embodiment of the roller compaction, the rollers are configured such that the first roller has an annual rim in such a configuration that the powder in the roller nip region is sealed off along the roller surface in the direction of the axis.

[0073] In one embodiment, the roller is constructed so that the nip region is sealed with a fixed plate along the roller surface in the axial direction. By ensuring that the nip region is sealed, powder losses at the axial ends of the roller are minimized compared to a completely cylindrical nip roller.

[0074] Due to the compaction of the lignin powder during the preparation of agglomerated lignin, the bulk density of lignin will increase with the pressure applied to the lignin powder. This means that the agglomerated lignin will have a higher bulk density than the lignin powder. During the subsequent processing into carbon-rich materials, tighter lignin particles may be beneficial, because it has been found that tight lignin particles maintain their shape without melting or expansion. The agglomerated lignin particles will also have a relatively higher hardness after compaction. Hard particles are advantageous during subsequent processing because they can resist physical impacts during processing. Further, when using hard, compacted particles, processing problems that may be caused by the presence of lignin dust on the particle surface are avoided. This is particularly important in large-scale processes because dust can form explosive mixtures with air and also cause blockages inside processing equipment.

[0075] The agglomerated lignin preferably has a 3 Up to 0.7g / cm 3 , more preferably 0.5 g / cm 3 Up to 0.6g / cm 3 The lignin powder preferably has a bulk density of 0.3 g / cm before agglomeration. 3 Up to 0.4g / cm 3 The bulk density is within the range of .

[0076] The agglomerated lignin has a particle size distribution such that at least 80% by weight of the particles have a diameter in the range of 0.2 mm to 5.0 mm. Preferably, the particle size distribution is such that at least 90% by weight, more preferably at least 95% by weight of the particles have a diameter in the range of 0.2 mm to 5.0 mm. More preferably, at least 90% by weight, more preferably at least 95% by weight of the particles have a diameter in the range of 0.5 mm to 2 mm.

[0077] In some embodiments, the lignin in the powder form is mixed with at least one additive before compaction. The mixing is carried out by methods and equipment known in the art. An example of a suitable method is a vertical mixer, such as a paddle, screw or ribbon mixer in batch or continuous mode. The mixing process can be carried out in a low, medium or high shear impact mode. Any suitable additive, such as a binder or lubricant, can be added to promote subsequent compaction processes and improve the density and mechanical properties of the agglomerated lignin obtained. In addition, additives having an impact on the properties of the final material, such as functional enhancement additives, can be added. The total amount of one or more additives is preferably less than 5 weight %, for example, less than 2 weight % based on the total dry weight of the mixture of lignin powder and one or more additives. When the agglomerated lignin is produced by the lignin powder mixed with additives, as described above about using only the lignin powder without additives, the compaction, crushing and optional screening steps are carried out.

[0078] In the embodiment in which lignin is provided in the form of agglomerated lignin, the at least one thermosetting resin is preferably provided in liquid form, and the step of forming the agglomerated lignin-thermosetting resin material involves coating the agglomerated lignin with the at least one thermosetting resin, to obtain the agglomerated lignin-thermosetting resin material. Any suitable method for coating known to those skilled in the art can be used, such as spraying or dipping. By coating the agglomerated lignin with the thermosetting resin, the outer layer of thermosetting resin is obtained on the agglomerated lignin-thermosetting resin material. After solidification, this provides a hard protective layer for the agglomerated lignin-thermosetting resin material, and the protective layer reduces the formation of dust, and any tendency of the agglomerated lignin-thermosetting resin material to adhere together due to melting / softening of the surface during subsequent heat treatment. The bulk density of the agglomerated lignin is not significantly affected by coating with a thermosetting resin.

[0079] In embodiments where the at least one thermosetting resin is in liquid form, the at least one thermosetting resin may be diluted with a solvent. If the thermosetting resin has a high viscosity, dilution of the thermosetting resin is preferably performed to facilitate subsequent coating steps. Any suitable solvent for the at least one thermosetting resin may be used, such as water, tetrahydrofuran or dichloromethane.

[0080] The agglomerated lignin-thermosetting resin material can be dried after coating. Drying can be carried out at room temperature or at an elevated temperature. Any suitable method known to those skilled in the art can be used for drying. Drying can be carried out under ambient pressure, reduced pressure, or vacuum. In some embodiments, drying is carried out for at least 10 hours at room temperature. In some embodiments, drying is carried out at one or more temperatures below 60°C, for example, in the range of 30°C to 60°C, for a time period in the range of 5 minutes to 10 hours. After drying, the dry content of the agglomerated wood thermosetting resin material is at least 50% by weight, for example, at least 70% by weight, or at least 80% by weight. In the embodiment where the thermosetting resin has been diluted with a solvent, the drying step is particularly important to remove the solvent.

[0081] If the agglomerated lignin-thermosetting resin material has not been dried prior to curing at elevated temperatures, drying will occur simultaneously with curing.

[0082] In one embodiment of the invention, the lignin provided in the method according to the first aspect is in powder form, wherein the particle size distribution of the lignin in powder form is such that at least 80% by weight of the particles have a diameter of less than 0.2 mm and a moisture content of less than 45% by weight. Preferably, the lignin in powder form is dried before further processing into agglomerated lignin. The drying of the lignin powder is carried out by methods and equipment known in the art. The lignin in powder form has a moisture content of less than 45% by weight. Preferably, the moisture content of the lignin powder is less than 25% by weight, preferably less than 10% by weight, more preferably less than 8% by weight. In one embodiment, the moisture content of the lignin powder is at least 1% by weight, for example at least 5% by weight. The temperature during drying is preferably in the range of 80°C to 160°C, more preferably in the range of 100°C to 120°C.

[0083] The lignin powder obtained after drying has a broad particle size distribution ranging from 1 μm to 2 mm, which is significantly skewed towards the micrometer range, meaning that a significant proportion of the particles have a diameter in the range from 1 to 200 micrometers.

[0084] In the embodiment in which the lignin is provided in powder form in the method according to the first aspect, the at least one thermosetting resin is preferably provided in powder form. The thermosetting resin powder can be obtained by freezing the thermosetting resin in liquid form and subsequently crushing it. The moisture content of the thermosetting resin in powder form is preferably less than 1% by weight.

[0085] In embodiments wherein both the lignin and the at least one thermosetting resin are provided in powder form, the step of forming the agglomerated lignin-thermosetting resin material preferably comprises the following steps:

[0086] i) mixing the lignin powder, the at least one thermosetting resin powder and optionally at least one additive to obtain a lignin-thermosetting resin mixture;

[0087] ii) compacting the lignin-thermosetting resin mixture obtained in step i) to obtain a lignin-thermosetting resin material;

[0088] iii) crushing the lignin-thermosetting resin material obtained in step ii) to obtain an agglomerated lignin-thermosetting resin material; and

[0089] iv) optionally sieving the agglomerated lignin-thermosetting resin material obtained in step iii) to remove particles having a particle size below 100 μm, thereby obtaining an agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm.

[0090] The mixing of the lignin powder, the thermosetting resin powder and optionally at least one additive is carried out by methods and equipment known in the art. An example of a suitable method is a vertical mixer, such as a paddle, screw or ribbon mixer in batch or continuous mode. The mixing process can be carried out in a low, medium or high shear impact mode. By ensuring that the mixing is sufficient, a good dispersion of at least one thermosetting resin of the lignin powder and powder form is achieved. A good dispersion then promotes further processing, and provides uniform properties for the lignin-thermosetting resin material obtained.

[0091] Optionally, at least one additive may be added during mixing. Any suitable additive may be added, such as a binder or lubricant, to facilitate subsequent compaction processes and to improve the density and mechanical properties of the agglomerated lignin-thermosetting resin material obtained. In addition, additives having an impact on the properties of the final material may be added, such as functional enhancement additives. The total amount of one or more additives is preferably less than 5 wt %, such as less than 2 wt %, based on the total dry weight of the mixture of lignin powder, thermosetting resin and one or more additives.

[0092] The compaction of the lignin-thermosetting resin mixture in step ii) is preferably carried out by roller compaction, and the roller compaction of the lignin-thermosetting resin mixture can be achieved by a roller compactor to agglomerate the material. In the compaction step, an intermediate product is generated. Here, fine powders of lignin and thermosetting resin are usually fed through a hopper and conveyed to a compaction zone by means of a horizontal or vertical feed screw, wherein the material is compacted into a thin sheet by a compaction roller with a defined gap. By controlling the feed screw speed, the pressure in the compaction zone develops, and a thin sheet with uniform density can be obtained. The pressure development in the compaction zone can preferably be monitored and controlled by the rotation speed of the compaction roller. When the powder is dragged between the rollers, it enters a place called the roller gap area, where the density of the material increases and the powder is converted into a thin sheet or ribbon. The roller used has a cavity. The depth of each cavity used for roller compaction is 0.1mm to 10mm, preferably 1mm to 8mm, more preferably 1mm to 5mm, or 1mm to 3mm. The specific pressure applied during said compacting may vary depending on the equipment used for compacting, but may be in the range of 1 kN / cm to 100 kN / cm.Apparatus suitable for carrying out compaction is known in the art.

[0093] After compaction, crushing is preferably performed. In the crushing step, the intermediate product from the compaction step is subjected to crushing or grinding, for example by means of a rotary granulator, a cage mill, an impact mill, a hammer mill, a crusher mill and / or a combination thereof. During this step, further intermediate products are generated.

[0094] After crushing, the crushed material is preferably subjected to a screening step to remove fine material. In addition, large materials, such as agglomerates with a diameter greater than 5.0 mm, can be removed and / or recycled back to the crushing step. In the screening step, the intermediate product from the crushing step is screened by physical classification, such as screening, also known as screening, to obtain a product, which is an agglomerated lignin-thermosetting resin material with a defined particle size distribution set by the porosity of the sieve or screen in this step. The sieve or screen is selected so that most of the particles with a diameter below 100 (or 500) μm pass through the sieve and are discarded, and preferably return to the compacting step, while most of the particles with a diameter above 100 (or 500) μm are retained and undergo a subsequent heating step according to the process of the present invention. The screening can be performed in more than one step, that is, the screening can be performed so that the crushed material from the crushing step passes through more than one sieve or screen in succession.

[0095] In one embodiment of the roller compaction, the rollers are configured such that the first roller has an annular edge in such a configuration that the powder in the region of the roller gap is sealed off along the roller surface in the direction of the axis.

[0096] In one embodiment, the roll is constructed so that the nip region is sealed with a fixed plate along the roll surface in the axial direction.By ensuring that the nip region is sealed, powder losses at the axial ends of the roll are minimized compared to a completely cylindrical nip roll.

[0097] Due to the compaction of the lignin powder and the thermosetting resin powder during the preparation of the agglomerated lignin-thermosetting resin material, the bulk density of the material will increase with the pressure applied to the powder. This means that the agglomerated lignin-thermosetting resin material will have a higher bulk density than the lignin powder and the thermosetting resin powder. During subsequent processing into carbon-rich materials, tighter lignin particles may be beneficial because it has been found that tight lignin particles maintain their shape without melting or expansion. The presence of the thermosetting resin in the agglomerate further improves the processability of the lignin. Therefore, the combination of the presence of the thermosetting resin together with the lignin in the agglomerate and the agglomeration process itself will cause the lignin material to be able to be heat treated while maintaining shape and not melting or expanding.

[0098] The agglomerated lignin-thermosetting resin material particles will also have a relatively higher hardness after compaction. Hard particles are advantageous during subsequent processing because they can resist physical impacts during processing. Further, when using hard, compacted particles, the processing problems that may be caused due to the presence of lignin dust on the particle surface are avoided. This is particularly important in large-scale processes because dust can form explosive mixtures with air and also causes obstruction inside the processing equipment.

[0099] In a preferred embodiment, the lignin provided in step a) of the method according to the invention is provided in a dry state, for example in the form of agglomerated lignin or in the form of a lignin powder. In such an embodiment, the lignin preferably also remains in a dry state when in contact with the thermosetting resin in step c). Preferably, the lignin does not dissolve during any step of the method of the invention.

[0100] According to a second aspect, the present invention relates to an agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm. The agglomerated lignin-thermosetting resin material comprises lignin and at least one thermosetting resin. The agglomerated lignin-thermosetting resin material may optionally include at least one additive. The agglomerated lignin-thermosetting resin material according to the second aspect can be obtained by a method according to the first aspect.

[0101] Preferably, the lignin in the agglomerated lignin-thermosetting resin material is kraft lignin, ie lignin obtained by the kraft process. Preferably, the kraft lignin is obtained from softwood or hardwood.

[0102] The type of thermosetting resin in the agglomerated lignin-thermosetting resin material is not particularly limited, and any suitable thermosetting resin can be used. In some embodiments, the thermosetting resin in the agglomerated lignin-thermosetting resin material is selected from furan resins such as polyfurfuryl alcohol, epoxy-based resins, phenolic resins such as bakelite, vinyl ester, melamine resins and polyimides. Preferably, the thermosetting resin is a furan resin, such as polyfurfuryl alcohol. In some embodiments, more than one thermosetting resin is selected.

[0103] In some embodiments, the total amount of thermosetting resin in the agglomerated lignin-thermosetting resin material is in a range of 1 wt % to 70 wt %, for example 1 wt % to 50 wt %, or 1 wt % to 20 wt %, or 1 wt % to 10 wt %, based on the total dry weight of the agglomerated lignin-thermosetting resin material.

[0104] The agglomerated lignin-thermosetting resin material according to the second aspect may be further defined as explained above with reference to the first aspect.

[0105] According to a third aspect, the present invention relates to a method for producing a carbon material. The method according to the third aspect involves providing an agglomerated lignin-thermosetting resin material obtainable by the method according to the first aspect, or an agglomerated lignin-thermosetting resin material according to the second aspect. The agglomerated lignin-thermosetting resin material and the method for producing the same are further defined as explained above with reference to the first aspect.

[0106] Thus, the method according to the third aspect may comprise performing the method according to the first aspect.

[0107] The method according to the third aspect also involves subjecting the agglomerated lignin-thermosetting resin material to heat treatment at one or more temperatures of 300°C to 3000°C. The heat treatment is carried out for a total time in the range of 30 minutes to 10 hours, that is, the residence time of the lignin-thermosetting resin material in the equipment for heat treatment is in the range of 30 minutes to 10 hours to obtain a carbon material. The obtained carbon maintains the shape of the agglomerated lignin-thermosetting resin starting material, that is, the agglomerated lignin-thermosetting resin material does not change its size or expand (sell) or melt during heat treatment. The resulting carbon material is suitable for use in, for example, energy storage applications, such as active materials in the negative electrode of a secondary battery.

[0108] As used herein, the term "heat treatment" refers to a process in which the agglomerated lignin-thermosetting resin material is heated at one or more temperatures for a sufficient time to increase the carbon content of the agglomerated lignin-thermosetting resin material and to convert the agglomerated lignin-thermosetting resin material into a carbon material. Depending on the temperature during the heat treatment, different types of carbon materials, such as charcoal or hard carbon, can be obtained from the agglomerated lignin-thermosetting resin material.

[0109] As used herein, the terms "carbon material" and "carbon-rich material" both refer to a material that is mostly composed of carbon, for example at least 80 wt%, or at least 90 wt%, or at least 95 wt%, and is obtained by carbonizing an organic compound.

[0110] The thermal treatment may be carried out at the same temperature throughout the thermal treatment, or may be carried out at a varying temperature, such as by gradually increasing the temperature or using a temperature gradient. The thermal treatment may include a temperature ramp from a starting temperature to a target temperature. The heating rate may be 1-100°C / minute. For example, before reaching the target temperature required for the carbonization of the lignin-thermosetting resin material, the thermal treatment may involve several intermediate temperatures with a temperature ramp between them. The thermal treatment may be carried out in a batch process or a continuous process. Any suitable reactor may be used, such as a rotary kiln, a moving bed furnace, a push plate furnace or a rotary hearth furnace. The thermal treatment is preferably carried out under an inert atmosphere, preferably a nitrogen atmosphere.

[0111] In some embodiments, the agglomerated lignin-thermosetting resin material provided is cured according to the method of the first aspect of the present invention and then directly heat treated. For example, the curing of the agglomerated lignin-thermosetting resin material can be first carried out at one or more temperatures in the range of 20°C to 250°C, such as 20°C to 200°C, or 20°C to 150°C, or 50°C to 150°C, and then the temperature can be increased to the temperature adopted during the heat treatment. The increase in temperature can be gradual or can include a temperature ramp. Therefore, in some embodiments, curing can be carried out in the same reactor as the subsequent heat treatment.

[0112] Preferably, the heat treatment comprises a preliminary heating step, preferably followed by a final heating step. The preliminary heating step is preferably carried out at one or more temperatures in the range of 300°C to 800°C, for example 500°C to 700°C. The preliminary heating step is preferably carried out under an inert atmosphere, preferably under a nitrogen atmosphere. The duration of the preliminary heating step is at least 30 minutes, and preferably less than 10 hours. The surface area of ​​the carbon material obtained after the preliminary heating step is typically between 300 and 700 m 2 / g range, using nitrogen as BET measurement.

[0113] The final heating step is preferably carried out at one or more temperatures in the range of 800°C to 3000°C. The final heating step is preferably carried out under an inert atmosphere, preferably a nitrogen atmosphere. The duration of the final heating step is at least 30 minutes and preferably less than 10 hours. After the final heating step is carried out above 1000°C, the surface area of ​​the obtained carbon material is typically 50 m 2 / g or less.

[0114] The preliminary and final heating steps may be performed as separate steps or as a single step in direct sequence. The preliminary and final heating steps may involve heating at one or more temperatures, as discussed above for the thermal treatment. For example, preheating is started at about 300°C and the temperature is subsequently increased to about 500°C. The final heating step is preferably performed between 900°C and 1300°C, for example at about 1000°C.

[0115] The preliminary and final heating steps can be carried out in a batch process or in a continuous process. Any suitable reactor can be used. The preliminary heating step and the final heating step can be carried out in the same reactor or in separate reactors.

[0116] In some embodiments, the method according to the third aspect further includes the step of grinding the agglomerated lignin-thermosetting resin material or the obtained carbon material. Grinding can be carried out before, during or after thermal treatment, and can be carried out on (cured) agglomerated lignin thermosetting resin material, or on the obtained carbon material. Alternatively, if the thermal treatment includes a preliminary heating step and a final heating step, grinding can be carried out after the preliminary heating step or after the final heating step. Several grinding steps can also be carried out. Grinding is carried out so that the average particle size is reduced. Grinding can be carried out by methods such as impact grinding, hammer milling, ball milling and jet milling. Optionally, fine / coarse particle selection can be carried out by classification and / or screening after grinding.

[0117] After heat treatment and optional grinding, the obtained carbon material can undergo further processing, such as carbon coating by chemical vapor deposition (CVD), pitch coating, thermal and / or chemical purification, further heat treatment, particle size adjustment and blending with other electrode materials to, for example, further improve its electrochemical properties.

[0118] The carbon material obtained by the method according to the third aspect is preferably used as an active material in the negative electrode of a non-aqueous secondary battery such as a lithium ion battery. When used to produce such a negative electrode, any method suitable for forming such a negative electrode can be used. In the formation of the negative electrode, the carbon-rich material can be processed together with other components. Such other components may include, for example, one or more adhesives that form the carbon-rich material into an electrode, conductive materials such as carbon black, carbon nanotubes or metal powders, and / or other Li storage materials such as graphite or lithium. For example, the adhesive may be selected from but is not limited to poly (vinylidene fluoride), poly (tetrafluoroethylene), carboxymethyl cellulose, natural butadiene rubber, synthetic butadiene rubber, polyacrylate, poly (acrylic acid), alginate, etc., or a combination thereof. Optionally, a solvent such as 1-methyl-2-pyrrolidone, 1-ethyl-2-pyrrolidone, water or acetone is used during processing.

[0119] According to a fourth aspect, the present invention relates to a carbon material obtainable by a method according to the third aspect. The carbon material obtainable by a method according to the third aspect is suitable for use in, for example, energy storage applications, such as an active material in a negative electrode of a secondary battery. The carbon material according to the fourth aspect may be further defined as explained above with reference to the third aspect.

[0120] According to a fifth aspect, the present invention relates to a negative electrode for a secondary battery, the negative electrode comprising as an active material a carbon material obtainable by the method according to the third aspect. The carbon material of the negative electrode according to the fifth aspect may be further defined as explained above with reference to the third aspect.

[0121] According to a sixth aspect, the present invention relates to the use of a carbon material obtainable by the method according to the third aspect as an active material in a negative electrode of a secondary battery.The carbon material of the sixth aspect may be further defined as explained above with reference to the third aspect.

[0122] Example

[0123] Example 1

[0124] The lignin powder from the LignoBoost process was agglomerated by roller compaction. The resulting agglomerated lignin had an average size in the range of 0.2 to 2.0 mm. The agglomerated lignin was coated with a liquid thermosetting resin so that the total amount of thermosetting resin in the resulting agglomerated lignin thermosetting resin material was 5 wt %. The material was dried at room temperature for 12 hours. The coated and dried agglomerated lignin was thermally cured using a stepwise sequence involving heating at 50° C. for 1 hour, heating at 70° C. for 1 hour, heating at 90° C. for 1 hour, and heating at 150° C. for 1 hour. The material gradually darkened during processing. After curing, the agglomerated lignin-thermosetting resin material was carbonized at 500° C. to 1400° C. under an inert atmosphere. The shape was maintained during carbonization, and no melting was observed.

[0125] Example 2 - Comparison

[0126] The lignin powder from the LignoBoost process is agglomerated by roller compaction. The resulting agglomerated lignin has an average size in the range of 0.2 to 2.0 mm. The agglomerated lignin is carbonized at 500° C. to 1400° C. under an inert atmosphere. The agglomerated lignin melts during carbonization and excessive foaming occurs.

[0127] In view of the above detailed description of the invention, other modifications and changes will become apparent to those skilled in the art. However, it should be apparent that such other modifications and changes can be achieved without departing from the spirit and scope of the invention.

Claims

1. A method for producing an agglomerated lignin-thermosetting resin material, wherein the method comprises the following steps: -providing lignin; - providing at least one thermosetting resin; - forming an agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm, wherein the forming involves contacting the lignin with the at least one thermosetting resin; and - Curing the agglomerated lignin-thermosetting resin material.

2. The method according to claim 1, wherein the lignin is provided in the form of agglomerated lignin having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm.

3. The method according to claim 2, wherein the agglomerated lignin provided is produced by a method comprising the steps of: a) providing lignin in powder form, wherein the lignin in powder form has a particle size distribution such that at least 80% by weight of the particles have a diameter of less than 0.2 mm and a moisture content of less than 45% by weight; b) compacting the lignin powder of step a); c) crushing the compacted lignin obtained in step b) to obtain agglomerated lignin; d) optionally sieving the agglomerated lignin obtained in step c) to remove particles having a particle size below 100 μm, thereby obtaining agglomerated lignin having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm.

4. The method according to claim 3, wherein the lignin in powder form is mixed with at least one additive before compacting.

5. A method according to any one of claims 2 to 4, wherein the at least one thermosetting resin is provided in liquid form, and wherein the step of forming an agglomerated lignin-thermosetting resin material involves coating the agglomerated lignin with the at least one thermosetting resin to obtain an agglomerated lignin-thermosetting resin material.

6. The method according to claim 5, wherein the at least one thermosetting resin is diluted with a solvent.

7. The method according to claim 5 or 6, wherein the agglomerated lignin-thermosetting resin material is dried after coating.

8. The method of claim 1, wherein the lignin is provided in powder form, wherein the lignin in powder form has a particle size distribution such that at least 80% by weight of the particles have a diameter of less than 0.2 mm and a moisture content of less than 45% by weight.

9. The method according to claim 8, wherein the at least one thermosetting resin is provided in powder form.

10. The method of claim 9, wherein the step of forming an agglomerated lignin thermosetting resin material comprises the steps of: i) mixing the lignin powder, the at least one thermosetting resin powder and optionally at least one additive to obtain a lignin-thermosetting resin mixture; ii) compacting the lignin-thermosetting resin mixture obtained in step i) to obtain a lignin-thermosetting resin material; iii) crushing the lignin-thermosetting resin material obtained in step ii) to obtain an agglomerated lignin-thermosetting resin material; iv) optionally sieving the agglomerated lignin-thermosetting resin material obtained in step iii) to remove particles having a particle size below 100 μm, thereby obtaining an agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm.

11. The method according to any one of the preceding claims, wherein the lignin is kraft lignin.

12. The method according to any one of the preceding claims, wherein the at least one thermosetting resin is selected from furan resins such as polyfurfuryl alcohol, epoxy-based resins, phenolic resins such as Bakelite, vinyl esters, melamine resins and polyimides.

13. The method according to any one of the preceding claims, wherein the total amount of thermosetting resin in the agglomerated lignin-thermosetting resin material is in the range of 1 to 70 wt. %, based on the total dry weight of the agglomerated lignin-thermosetting resin material.

14. A method according to any preceding claim, wherein curing is carried out at one or more temperatures in the range of 20°C to 250°C for a total time of at least 30 minutes.

15. The method according to any one of the preceding claims, wherein an acidic catalyst is added to the thermosetting resin, and wherein curing of the agglomerated lignin-thermosetting resin material is catalyzed by the acidic catalyst.

16. An agglomerated lignin-thermosetting resin material having a particle size distribution such that at least 80% by weight of the agglomerates have a diameter in the range of 0.2 mm to 5.0 mm.

17. The agglomerated lignin-thermosetting resin material according to claim 16, wherein the lignin in the agglomerated lignin-thermosetting resin material is kraft lignin.

18. The agglomerated lignin-thermosetting resin material according to any one of claims 16 or 17, wherein the thermosetting resin in the agglomerated lignin-thermosetting resin material is selected from furan resins such as polyfurfuryl alcohol, epoxy-based resins, phenolic resins such as bakelite, vinyl esters, melamine resins and polyimides.

19. The agglomerated lignin-thermosetting resin material according to any one of claims 16 to 18, wherein the total amount of thermosetting resin in the agglomerated lignin-thermosetting resin material is in the range of 1 to 70 wt% based on the total dry weight of the agglomerated lignin-thermosetting resin material.

20. A method for producing a carbon material, the method comprising the steps of: - providing an agglomerated lignin-thermosetting resin material obtainable by the method according to any one of claims 1 to 15 or an agglomerated lignin-thermosetting resin material according to any one of claims 16 to 19; - subjecting the agglomerated lignin-thermosetting resin material to a heat treatment at one or more temperatures in the range of 300°C to 3000°C, wherein the heat treatment is carried out for a total time in the range of 30 minutes to 10 hours, to obtain a carbon material.

21. The method of claim 20, wherein the heat treatment comprises a preliminary heating step followed by a final heating step.

22. The method of claim 21, wherein the preliminary heating step is performed at one or more temperatures in the range of 400°C to 800°C for at least 30 minutes.

23. The method according to any one of claims 21 or 22, wherein the preliminary heating step is performed under an inert atmosphere.

24. The method according to any one of claims 21 to 23, wherein the final heating step is carried out at one or more temperatures in the range of 800°C to 3000°C for at least 30 minutes.

25. The method according to any one of claims 21 to 24, wherein the final heating step is performed under an inert atmosphere.

26. The method according to any one of claims 20 to 25, wherein the method comprises an additional step of grinding the agglomerated lignin-thermosetting resin material or the obtained carbon material.

27. Carbon material obtainable by the method according to any one of claims 20-26.

28. A negative electrode for a secondary battery, comprising a carbon material obtainable by the method according to any one of claims 20 to 26 as an active material.

29. Use of a carbon material obtainable by a process according to any one of claims 20 to 26 as an active material in a negative electrode of a secondary battery.

Citation Information

Patent Citations

  • Method for separating lignin from black liquor

    WO2006031175A1

  • Process for producing carbon from heat treated lignin

    WO2021250604A1